2009
DOI: 10.1123/japa.17.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Successful Aging in Canadian Older Adults

Abstract: Rowe and Kahn (1987) proposed that successful aging is the balance of three components: absence of disease and disease-related disability, high functional capacity, and active engagement with life. This study examines the relationship between physical activity involvement and successful aging in Canadian older adults using data from the Canadian Community Health Survey, cycle 2.1 (N = 12,042). Eleven percent of Canadian older adults were aging successfully, 77.6% were moderately successful, and 11.4% were unsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 21 publications
6
63
0
Order By: Relevance
“…It can be influenced by biological, psychosocial, and environmental factors [3,[18][19][20][21][22][23][24][25][26]. However, sociocultural components of a country-level OLE mentioned above have not been studied in relation to socio-ecological inequality indicators.…”
Section: Introductionmentioning
confidence: 99%
“…It can be influenced by biological, psychosocial, and environmental factors [3,[18][19][20][21][22][23][24][25][26]. However, sociocultural components of a country-level OLE mentioned above have not been studied in relation to socio-ecological inequality indicators.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely acknowledged that PA participation has many benefits for older adults and should be an important part of health promotion initiatives for this population (Menec, 2003;Belza et al, 2004;Baker et al, 2009;King and King, 2010). It could be argued that government and non-governmental organizations should invest in areas other than PA, given the many other health, social, economic, physical, and political issues concerning older adults, such as elder abuse, poverty, disability, ageism, inadequate living conditions, and isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, PA can have a significant impact on physical, mental, social, cultural, and economic aspects of older adults' lives (Menec, 2003;Belza et al, 2004;King and King, 2010). As a result, there are compelling reasons for government and non-governmental organizations alike to address PA for older adults in their policies and to invest in and encourage programs and opportunities to promote PA. Baker et al (2009) found that in the 2003 Canadian Community Health Survey, Canadian older adults who were physically active were about twice as likely to be rated as successfully aging in comparison to those who were not physically active. Even after adjusting for age, sex, and income, PA was a significant predictor of successful aging, which these authors defined as a balance of three components: "low probability of disease and disease-related disability, high cognitive and physical functional capacity, and active engagement with life" (Baker et al, 2009:224).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rowe and Khan's [26] model of SA has been the most commonly used and widely accepted in research [1,26]. They reported that most aging research focuses on "losses"; leading many geriatricians to believe that decreases in cognitive and physical function are simply a product of aging, even when disease and pathology are absent.…”
mentioning
confidence: 99%